Aplicación de técnicas de recolección y conservación de granos de polen en Sacha Inchi (Plukenetia Volubilis l.) en la zona de Bello Horizonte, Distrito de la Banda de Shilcayo - región San Martín - Risco Vargas, Manuel Yampaolo (2008)
With the object of find and / or to determine a methodology for the collection and preservation of pollen grains of Sacha inchi (Plukenetia volubilis L.), were taken into account two phonological stages of flowering. The first stage before anthesis and the second stage after anthesis, this in order to know the behavior of both phases of flowering and viability of pollen grains with respect to germination and formation of fruit. The excellent preservation of pollen grains, shows that both the collection and preservation method used in this research work are the most optimal and appropriate. We use one of the most important parameters for temperature (T°), two scales as 8 º C and -8 º C, which responded excellently to the action to conserve the pollen grains, while in a perfect state of dormancy SUS morphological, physiological and genetic, so make use of both methods because it demonstrated the high reliability of these. The germination percentage is determined by counting an approximate number of germinated pollen grains (100 grains), using a culture medium proposed by Taylor, 1972. Which after several tests along with other proposals, was offered the best results. The media fulfills the role of stigma in a host to complete development of pollen grains and only those meeting the conditions is that one to form the gynoecium and fruit tress.